The clinical study of high-intensity focused ultrasound for the treatment of 160 cases of postpartum placenta increta - Xiaogang Zhu; Xin Sun; Mingzhu Ye; Min Xue (International Journal of Hyperthermia)
Purpose To investigate the safety and efficacy of high-intensity focused ultrasound (HIFU) in the treatment of postpartum placenta increta and to analyze the influencing factors of intraoperative blood loss and curettage times.Methods From January 2016 to December 2018, a retrospective analysis was conducted on 160 patients with placenta increta treated by HIFU combined with (or without) curettage in our hospital. Intraoperative blood loss and the number of curettage procedures were recorded. The clinical outcomes and the influencing factors of bleeding and the number of curettage procedures were analyzed.Results No serious complications occurred during HIFU treatment. The median volume of blood loss during suction curettage was 20 ml (range: 5–600 ml). Blood loss was significantly higher in patients with a large placental diameter (p = 0.007). The risk of requiring multiple curettage procedures was significantly higher in patients with a large placental diameter (p = 0.023). The interval time between HIFU and suction curettage was identified as a protective factor, a longer interval was associated with fewer curettage procedures (p = 0.015).Conclusion Based on the results of our large-sample study, HIFU appears to be safe and effective in the treatment of postpartum placenta increta. Blood loss volume is associated with the largest diameter of the placenta. The risk of requiring multiple curettage procedures is related to the largest diameter of the placenta, While the interval time between HIFU and suction curettage is a protective factor for reducing curettage times.